Penggunaan data analytics dalam analisis kinerja keuangan - Anandita Putri; Nabilla Sabina; Ningrum Pramudiati (Qualitative Research of Business and Social Sciences, 2025)
Digitalization of industrial processes offers companies opportunities to enhance operational performance, primarily through data analytics. Data analytics is a method for analyzing data to gain insights that support resource efficiency and improve a company's financial performance. This study aims to investigate the financial performance of PT Aneka Tambang Tbk using profitability ratios, namely NPM, ROA, and ROE, and to determine whether data analytics can simplify and represent the company's financial performance. Although profitability ratio analysis is widely practiced, data analytics for financial performance analysis remains rare. This study employs a qualitative method, using secondary data from annual reports published on the Indonesia Stock Exchange and the company's official website. Data collection techniques involve documentation methods. The analysis results indicate that the financial performance of PT Aneka Tambang Tbk in 2014 - 2023 is considered suboptimal, as the average NPM, ROA, and ROE remain below industry standards. Data analytics in financial performance analysis can simplify and more effectively represent financial performance.